Dramaturgies of Contagion in Contemporary British Speculative Theatre - June Xuandung Pham (Centre de Recherche "Texte et Critique de Texte", 2021)
This article looks at three contemporary British speculative plays – Dawn King’s Foxfinder (2011), Stef Smith’s Human Animals (2016) and Alistair McDowall’s X (2016) – to show how their approach to the theme of transmission interrogates the simplified forms of contagion based on binary categories such as present/absent, before/after, cause/symptom, human/nonhuman. It is my belief that these plays’ conception of contagion, not as a mere epidemiological fact but as a metaphor for disruption and relationality, transformation and conformity, invokes a distinct utopian method of the twenty-first century, which is best characterised by uncertainty.